Development of high-protein and micro-mineral food products as an alternative snack for pregnant women in East Nusa Tenggara - Loaloka, Meirina S; Adi, Anak Agung Ayu Mirah; Costa, Santa Luciana Da; Lestaluhu, Santi; Soumokil, Oktavia (Institute of Computer Science (IOCS), 2025)
The World Health Organization (WHO) reports that the prevalence of CED in pregnant women globally is 35-37% which is significantly higher in the 3rd trimester compared to the first and second trimesters of pregnancy. Efforts to develop food ingredients are very necessary. This research was conducted to prove the impact of providing high protein food made in the form of sokateri milk pie which was substituted for anchovy flour, peanuts, green beans and sorghum. This research used a completely randomized design, namely with 5 treatments with 1 standard treatment. Total Energy from the five milk pie treatments, namely P0 465.02%, P1 462.36%, P2 463.22%, P3 428.80%, P4 423.35%, and vitamin C levels in treatments P0 to P4 were not there is Vitamin C content in the product, the Fe content is 3.42%, and the calcium content is 126.91%, pie milk has met SNI 01-42701996 standards, for the best acceptability of milk pie in terms of color, taste, aroma and texture, namely with milk pie in the P2 treatment.